Nilai Profil Pelajar Pancasila dalam Novel Laut Bercerita Karya Leila S. Chudori - Salma Rasyidah, Aisyah (Transformatika: Jurnal Bahasa, Sastra, dan Pengajarannya, 2024)
The Pancasila Learner Profile was a framework of characters and competencies that learners in Indonesia were expected to possess, in accordance with the values of Pancasila as the nation's foundation and worldview. The values of Pancasila included respect for Bhinneka Tunggal Ika (unity in diversity), the spirit of gotong royong, social justice, democracy, and the moral values contained in Pancasila. This research aimed to elaborate on issues related to the value of the Pancasila Student Profile contained in the novel Laut Bercerita by Leila S. Chudori. This research used a qualitative method of content analysis with an interactive data analysis technique of the Miles and Huberman model. Data on the value of the Pancasila Student Profile were taken from primary data in the form of content and dialogue contained in the novel Laut Bercerita. This research found the value of the Pancasila Student Profile in 5 characters in the novel Laut Bercerita by Leila S. Chudori, namely Biru Laut, Asmara Jati, Biru Laut, Alex Perazon, and Romo Felix. The value of the Pancasila Student Profile was a behavior that showed an attitude in practicing the values of Pancasila in everyday life. Practicing the values of Pancasila in everyday life was reflected in the attitude of practicing religious teachings, tolerance for existing differences, being able to think critically and creatively in facing existing challenges, being able to be independent and responsible, and being able to work together with others.